Rajata jayantī smrti-grantha - Vaṃśīdhara Vidyāmārtaṇḍa; Pandey, Rajkishor, 1920- (Hindī Pracāra Sabhā, 1966)
Silver jubilee souvenir of the Hindi Prachar Sabha, Hyderabad, India; articles on Hindi language and literature, and the Sabha's activities.